A contribution to Porogramme (Polyporaceae, Agaricomycetes) and related genera - Wei-Lin Mao; Ying-Da Wu; Hong-Gao Liu; Yuan Yuan; Yu-Cheng Dai (IMA Fungus)
Abstract The polypores with shallow pores from tropical Asia and America are studied. Our molecular phylogeny based on the internal transcribed spacer (ITS), the large subunit nuclear ribosomal RNA gene (nLSU), the translation elongation factor 1-α gene (TEF1), and the largest subunit of RNA polymerase II (RPB1) demonstrates six clades are formed among Porogramme and related genera. Two new genera, Cyanoporus and Pseudogrammothele, are established, and the six clades represent Porogramme , Cyanoporus , Grammothele, Epithele, Theleporus, and Pseudogrammothele, respectively. The molecular clock analyses estimate the divergence times of the six clades based on a dataset (ITS + LSU + TEF1 + RPB1 + RPB2), and we recognize the mean stem ages of the six genera are earlier than 50 Mya. Three new species in Porogramme were morphologically and phylogenetically confirmed, and they are described as P. austroasiana, P. cylindrica, and P. yunnanensis. Phylogenetic analysis shows that type species of Tinctoporellus and Porogramme are nested in the same clade, and Tinctoporellus is treated as a synonym of Porogramme. Based on our phylogeny, twelve new combinations are proposed, and the differences between the new species and similar or related species are discussed.